An interval gas flow analysis in natural gas and electricity coupled networks considering the uncertainty of wind power. (1st September 2017) - Qiao, Zheng; Guo, Qinglai; Sun, Hongbin; Pan, Zhaoguang; Liu, Yuquan; Xiong, Wen
Highlights: A comprehensive model of natural gas and electricity coupled networks is built. Two methods on the uncertainty analysis using interval algorithm is proposed. The interval solutions can provide great insights into the coupled systems. An accessible capacity model of wind power under gas network constraints is built. Abstract: The wide application of renewable energy sources in power systems has a significant influence on both electrical and tightly coupled systems. The aim of this paper is to build a comprehensive system model of a natural gas and electricity coupled network. The concept of distributed stack nodes was introduced to overcome the shortcoming of adjusting active power by a single gas-fired unit to achieve power balance. On this basis, the impact of the active power output uncertainty of wind farms was studied, and the interval flow of the natural gas system was analyzed by two proposed methods. The results were compared with Monte Carlo stochastic simulation. Case studies demonstrated the effectiveness of the proposed method and led to the conclusion that the uncertainty of wind power has a significant impact on the steady-state operation of natural gas systems. Interval solutions could provide great insights into the operating and planning of coupled systems with wind power uncertainty.